Performing two different actions simultaneously: The critical role of interhemispheric interactions during the preparation of bimanual movement. (April 2016) - Fujiyama, Hakuei; Van Soom, Jago; Rens, Guy; Cuypers, Koen; Heise, Kirstin-Friederike; Levin, Oron; Swinnen, Stephan P.
Abstract: Even though it has been suggested that the dorsolateral prefrontal cortex (DLPFC) and dorsal premotor cortex (PMd) are highly involved in the planning of bimanual movements, the exact nature (facilitatory or inhibitory) of their role is not well understood. Using a dual-site transcranial magnetic stimulation (TMS) paradigm, we examined the functional influence from DLPFC and PMd to the contralateral primary cortex (M1) during the preparation of a complex bimanual coordination task in which inter-hand movement frequency was manipulated. Only the left PMd showed inter-hand frequency-specific modulations in the interaction with the contralateral M1. Left PMd-right M1 interaction became facilitatory during the preparation phase when the left hand had to move faster than the right hand, while inhibitory modulation was observed when the movement frequency arrangement was reversed. Interestingly, bilateral DLPFC showed a facilitatory interaction with the contralateral M1s during the preparation period only in difficult conditions, irrespective of the inter-hand frequency ratio, suggesting a less task-specific role in the organization of complex bimanual actions. Observed task-related modulations in DLPFC-M1 and left PMd-right M1 interactions during preparation were significantly correlated with up-coming performance, predicting successful bimanual movements. These observations highlight the distinct roles of DLPFC and left PMd in the preparation of bimanual movements that require a differential contribution of each limb.